Peculiarities of high-temperature plastic straining anisotropy in with NaCl type single crystals in creep conditions - Matsokin, D.V.; Pakhomova, I.N.; Matsokin, V.P. (Functional Materials, 2005)
The peculiarities of high-temperature creep anisotropy of NaCI and KCI single crystals have been studied under two stressed states. The relationship between the number of active easy slip systems and the straining rate has been established. The conditions of dislocation reactions in NaCI type single crystals and the results of dislocation interactions have been considered. Дослiджено особливостi високотемпературної повзучостi монокристалiв NaCl та KCI при двох видах напруженого стану. Встановлено зв'язок помiж кiлькiстю систем легкого ковзання та швидкiстю деформування. Проаналiзовано умови, за яких дислокацiйнi реакцiї у кристалах з граткою типу NaCl можуть мати мiсце, та результати взаємодiї дислокацiй. Исследованы особенности анизотропии высокотемпературной ползучести монокристаллов NaCI и KCI при двух видах напряженного состояния. Установлена связь между числом действующих систем легкого скольжения и скоростью деформации. Проанализированы условия прохождения дислокационных реакций в кристаллах типа NaCI и результаты взаимодействия дислокаций.